2010
DOI: 10.1007/s00244-010-9621-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Organochlorine Pesticide Endosulfan on GnRH and Gonadotrope Cell Populations in Fish Larvae

Abstract: Endocrine-disrupting chemicals can influence the hypothalamus-pituitary-gonad axis and possibly affect reproduction in vertebrates. We analyzed the effect of 30-day endosulfan (ES) exposure in sexually undifferentiated larvae of the cichlid fish Cichlasoma dimerus. The number, area, mean cytoplasmic and nuclear diameter, and mean cytoplasmic optical density of gonadotropin-releasing hormone (GnRH) I, II, and III immunoreactive (ir-) neurons and β follicle-stimulating hormone (βFSH) ir-cells were measured. Anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 44 publications
3
22
2
1
Order By: Relevance
“…Since there are no tests available for measuring pituitary hormones in the plasma of non-salmonid species, the methods used are a valid substitute to evaluate pituitary hormones during the annual reproductive cycle in S. parahybae. Similar analyses were performed in other teleost species: C. dimerus (Fiszbein et al, 2010;Piazza et al, 2011;Tubert et al, 2012), S. hilarii (Honji et al, 2013a). Moreover, despite nuclear diameter being a useful tool to analyze neuron activity (Fiszbein et al, 2010;Piazza et al, 2011), as no differences in nuclear diameter were observed in this study, the morphometric analysis was based mainly on the OD and the cellular diameter as indicative of higher or lower cellular activity during the reproductive cycle of S. parahybae.…”
Section: Discussionsupporting
confidence: 56%
“…Since there are no tests available for measuring pituitary hormones in the plasma of non-salmonid species, the methods used are a valid substitute to evaluate pituitary hormones during the annual reproductive cycle in S. parahybae. Similar analyses were performed in other teleost species: C. dimerus (Fiszbein et al, 2010;Piazza et al, 2011;Tubert et al, 2012), S. hilarii (Honji et al, 2013a). Moreover, despite nuclear diameter being a useful tool to analyze neuron activity (Fiszbein et al, 2010;Piazza et al, 2011), as no differences in nuclear diameter were observed in this study, the morphometric analysis was based mainly on the OD and the cellular diameter as indicative of higher or lower cellular activity during the reproductive cycle of S. parahybae.…”
Section: Discussionsupporting
confidence: 56%
“…Other effects of OCPs on GnRH neurons have been reported using in vivo experimentation. Cichlid fish ( Cichlasoma dimerus ) larvae exposed to a sub-lethal concentration of 0.1 µg/L endosulfan for 30d showed decreased nucleus/cytoplasm area ratio for GnRH1 neurons whereas pituitary follicle stimulating hormone cells showed a significant increase in nuclear size and mean nuclear diameter (Piazza et al, 2011). The authors hypothesized that these changes may be sufficient to affect sexual differentiation and adult reproduction.…”
Section: Legacy Pesticides As Neuroendocrine Disruptorsmentioning
confidence: 99%
“…The HPG axis regulates gonadal development and reproduction in fish [19]. The principal HPG axis neurohormone secreted by the hypothalamus is gonadotropin releasing hormone (GnRH).…”
Section: Introductionmentioning
confidence: 99%